Understanding Curriculum through the Concerns of Marginalised - Patel, Divyanshu (JOURNAL OF INDIAN EDUCATION, 2019)
The paper engages with the term curriculum, and attempts to understand how it becomes an instrument of exclusion and divisiveness. This paper reflects on how the dilution of curricular goals has a deleterious impact and how curriculum transaction tends to reinforce the existent social hierarchies. The paper also briefly discusses about the key curricular recommendations of NCF 2005, Kothari Commission (1964) and Yashpal Committee Report (1993) particularly with respect to the representation of the marginalised in the Indian educational scenario. The discussion is done in light of concerns about the oppressed classes voiced in the Mandal Commission Report (1980). In this paper, an attempt has been made to delve into the underlying concerns that characterise developing a curriculum, particularly in the Indian context. Section 1 of the paper is an exploration of the term curriculum. It is pertinent to delve into the same as it forms the basis of understand how divisiveness and sectarian interests permeate the framing of the curriculum. Key aspects of this dimension are discussed in Section 2. Drawing insights from research studies on curricular framing and policy outlook (discussed in Section 3), an attempt has been made to explore how textbooks are often non-neutral, biased and are influenced by the socio-political factors and interests of dominant groups in the society. This analysis draws upon insights from policy initiatives such as the National Curriculum Framework (NCF 2005), reports and the efforts made to make education more inclusive, as elaborated in Position Papers on SC and ST by National Curriculum Framework (NCF 2005).